An assessment of challenges of administering turnover tax collection: a case study of Kenya Revenue Authority - Karanja, James Kairu (Strathmore University, 2018)
Turnover Tax (TOT) was introduced in Kenya in the 2006 Finance Act, and rolled out in January 2007. TOT was designed as a presumptive tax or estimate charge computed at 3% of the sales turnover of businesses making Kshs. 5 million or less. This step was designed as a revenue measure to broaden the tax base by bringing the largely untapped informal sector into the tax base. More than 10 years on the tax gap from the informal sector indicates the collections at a meagre 0.15% of the true tax potential. This study is focused on challenges faced by Kenya Revenue Authority, the single collector of national government revenue, in administering the TOT. The objectives of the study were; to assess the perceptions by KRA officers of application of trust and facilitation measures in collection of TOT in Nairobi Kenya; assess the perceptions by KRA officers of extent of application of enforcement measures in collection of turnover taxation of the informal sector; and based on the responses to identify priority areas for policy, legal and KRA administrative reform in collection of tax from the informal sector. The study identified the independent variables for this research to be trust and facilitation (simplification and education/advice) and enforcement (powers and procedures, detection capabilities and punishment). A target population of 235 KRA staff was selected and a total sample size of 147 was selected as representative, to be the focus of this study. A descriptive survey design was used. Stratified sampling technique was used to create a sampling frame ensuring that all Nairobi Domestic Tax Department (DTD) offices were included in the survey. Data was collected using self–administered questionnaires and direct interviews. Statistical Package for Social Scientist software (SPSS version 20) was used to perform descriptive and inferential analysis on the collected data, and findings presented using tables. The principal findings were that KRA has been hampered in its efforts to implement the policy on informal taxation largely due to lack of adequate resources, a poorly implemented strategy of taxpayer facilitation and lax enforcement among the informal sector largely leading to lower than expected tax gains from TOT. The study could not establish positive effects of the KRA radical shift towards trust and facilitation on the TOT collections since the launch of the 6th Corporate Plan in 2015. The study finds that a more focused investment by KRA in reviewing powers and procedures, detection of non-compliant taxpayers and punishing of those who wilfully comply has the potential of increasing the TOT revenue base.
Keywords: Turnover Tax; Presumptive tax; Informal sector; Kenya Revenue Authority